2016
DOI: 10.1177/0268355516655067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TGF-beta1 on MMP/TIMP and TGF-beta1 receptors in great saphenous veins and its significance on chronic venous insufficiency

Abstract: Objectives Transforming growth factor-beta1 (TGF-β1) may participate in local chronic inflammatory processes in varicose veins and in venous wall structure modifications through regulation of matrix metalloproteinases (MMP) and their inhibitors (tissue inhibitor of metalloproteinase (TIMP)). The aim of this study was to analyze the effect of TGF-β1 in the vein wall, namely on the gene expression of selected MMP, TIMP and TGF-β1 receptors. Methods Healthy vein samples were harvested from eight subjects who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…We have previously demonstrated that TGF-β1 may directly intervene in the gene expression of MMP/TIMP in the great saphenous vein wall [ 30 ], which reinforced the hypothesis that the inflammatory process may lead to morphologic changes within the vein wall that is mediated by MMP and TIMP expression/activity [ 8 , 12 , 31 ]. Increasing knowledge about TGF-β1 signaling mechanisms and regulation indicates that signaling responses are extensively defined by TGF-β1 receptor availability and function [ 10 , 32 ].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…We have previously demonstrated that TGF-β1 may directly intervene in the gene expression of MMP/TIMP in the great saphenous vein wall [ 30 ], which reinforced the hypothesis that the inflammatory process may lead to morphologic changes within the vein wall that is mediated by MMP and TIMP expression/activity [ 8 , 12 , 31 ]. Increasing knowledge about TGF-β1 signaling mechanisms and regulation indicates that signaling responses are extensively defined by TGF-β1 receptor availability and function [ 10 , 32 ].…”
Section: Introductionmentioning
confidence: 79%
“…For complementary deoxyribonucleic acid (cDNA) synthesis, 500 ng of total RNA was reverse transcribed using the M-MuLV Reverse Transcriptase kit (NZYTech ® , Lisbon, Portugal) in a final volume of 20 mL. Both procedures have been described elsewhere [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Depletion of vein elastic components is a common observation in the venous wall of elderly and CVI patients (particularly, during the disease later stages) [ 116 , 127 ] that was related to decreased elastin synthesis and increased elastase activity, which in turn could be a consequence of elastic tissue modulators (such as LTBP and TGF-β1) attempt to stabilize elastin expression in regions of extensive injury [ 116 ]. In addition, some authors suggested that abnormalities in ECM structure leading to decreased elasticity and increased distensibility of the venous wall result from an imbalance between MMP (endopeptidases involved in the degradation of several ECM proteins) and TIMP (their endogenous inhibitors) [ 12 , 15 , 16 , 18 , 112 , 128 ], which are regulated at both transcriptional and post-transcriptional levels by various cytokines or growth factors, including TGF-β1 [ 15 , 118 ] ( Figure 4 ). In reverse, MMP upregulation may also promote growth factor release (by cleaving growth factor-binding proteins) and this may partly explain the VSMC hypertrophy observed in some parts of the hypertrophic regions of varicose veins [ 18 ].…”
Section: The Role Of Tgf-β1 Signaling Pathways In Vessel Wall Pathmentioning
confidence: 99%
“…Decreasing the amount of active TGFβ causes smooth muscle cells to undergo apoptosis, but adding exogenous TGFβ has no benefi cial eff ect [37], while gene expression of MMP9, MMP12, TIMP1 and TIMP2 is infl uenced by the addition of TGF-β1. Th ese results may be translated to chronic venous insuffi ciency framework and suggest involvement of TGF-β1 in the vein wall pathology [38].…”
Section: Discussionmentioning
confidence: 85%